The feasibility of trust as a generation skipping device based on the amendments to the Income Tax Act and the Davis tax committee's report into wealth taxation as well as the potential effect these may have on trusts - Crafford, Carel Pieter (My University, 2019)
Trusts are not as desirable as they once were, and every year they seem to become less so. The reason for their increasing undesirability is the heavy tax burden they carry.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Commerce (specialising in Taxation)
Keywords: UCTD; Wealth tax; Trusts; High net worth of individual; Tax on trusts; Transfer pricing; Double taxation--South Africa; Trusts and trustees--Taxation--South Africa; Income tax--Law and legislation--South Africa; SDG-8: Decent work and economic growth